Methods of Cultivation and Crop Productivity in Rain-fed Mechanized Schemes in Sennar State, Sudan (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to obtain baseline informationabout the methods of cultivation and crop productivity in the RainfedMechanized Schemes (RMS) in Sennar State. Forty farmers were selectedfrom Eldindir, Singa and Sennar localities. The data collected was in theform of questionnaires, meetings and group discussion with farmers. Thequestionnaire was designed to obtain information about the area perscheme, areas allocated for cultivation, cultural practices, crops grown,and their yields. SSPS software programme was used for data analysis.The results revealed that the largest scheme areas were at Singa followedby EL Dindir and the smallest areas were at Sennar. Farmers at Sennarallocate all the area for crop cultivation, whereas at EL dindir and Singa,53.4 and 66.7% of the farmers allocate area for cropping and the rest forforest, respectively. Sorghum and millet are grown in all localaties, whilesesame and sunflower are grown only at EL dindir and Singa localities.Land preparation in all locations started by clearance of trees andperennial bunch grasses. Sowing is by wide level disc planter in ELDindir and Singa, while in Sennar, sowing is by seed broadcast andridging. In all localities weeding is manually after two or three weeksfrom sowing and some farmers use herbicides in combination withmanual weeding. None of the farmers use fertilizers and pesticides. Noproper crop rotation is applied in all localities. All farmers harvestsorghum and millet manually and mechanical threshing, while sesame isharvested manually and sunflower mechanically. The yields of all growncrops are low and not exceeding an average of 414, 252, 207 and 255 kgseeds per feddan for sorghum, millet, sesame and sunflower,respectively.
Keywords: Sennar State rain-fed; mechanized farming; mechanized schemes